A Novel Tripod Percutaneous Reconstruction Technique in Periacetabular Lesions Caused by Metastatic Cancer. (1st April 2020) - Yang, Rui; Goch, Abraham; Murphy, Dennis; Wang, Jichuan; Charubhumi, Vanessa; Fox, Jana; Sen, Milan; Hoang, Bang; Geller, David
Abstract : Background: Metastatic lesions in the periacetabular region can cause pain and immobility. Symptomatic patients are often treated surgically with a total hip replacement using various modified Harrington methods. These open surgical procedures confer inherent risks. Prolonged recovery and potential complications may delay adjuvant radiation and systemic therapy. Methods: We describe a novel technique for acetabular reconstruction. Three large-bore cannulated screws are placed percutaneously under fluoroscopy in a tripod configuration to reinforce the mechanical axes of the acetabulum. Increased stability improves pain control and permits weight-bearing. Results: Twenty consecutive patients with periacetabular metastases were treated using the tripod technique. Eighteen patients (90%) had Harrington class-III lesions, and 2 patients had Harrington class-II lesions. The mean surgical time was 2.3 hours. Sixteen patients (80%) were able to get out of bed on postoperative day 1. At 3 months postoperatively, there was significant improvement in pain as documented on their visual analog scale (p < 0.01) and in functionality as measured by the Eastern Cooperative Oncology Group score (p < 0.01). The mean follow-up time was 7 months (range, 0.6 to 20 months). At the most recent follow-up, only 3 among the 16 surviving patients were using opioids chronically for pain. Total hip arthroplasty was performed in 4 patients (20%) in a staged fashion using the previously placed screws as support for a cemented cup and obviating the need for a cage device. Of the 16 patients, 15 could walk either independently (6 patients) or using an ambulatory aid (9 patients). Eight patients with the primary tripod reconstruction survived >6 months postoperatively. They were found to have either new bone formation filling the defects or healing of the pathological fractures. There has been no implant loosening or failure. Conclusions: The tripod technique is a novel application to provide safe and effective pain relief in the context of periacetabular metastatic disease. It can be easily converted to support a cemented acetabular cup for a total hip replacement should disease progression occur. This technique provides an alternative to open surgery as currently practiced in these patients. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.